Design and validation of a multiplex PCR protocol for microsatellite typing of Candida parapsilosis sensu stricto isolates - Trobajo-Sanmartín, Camino (2018)
Analysis of polymorphic microsatellite markers (STR) is a helpful genotyping technique to differentiate Candida parapsilosis sensu stricto isolates. The aim of this study is to develop and perform an initial validation of an alternative protocol for the reliable and accurate microsatellite genotyping of C. parapsilosis sensu stricto isolates using high-throughput multiplex PCR. To achieve this, the results obtained using the new protocol were compared to the ones obtained using a previously described reference method. To that end, diagnostic accuracy, informativeness and discrimination parameters were estimated.